Avian diversity during rehabilitation stage of Chimdi Lake, Sunsari, Nepal - Surana, R; Subba, BR; Limbu, KP (Our Nature, 2008)
Avian diversity of Chimdi Lake during rehabilitation stage was studied. 109 species of birds belonging to 34 families were recorded. Maximum 64 species were recorded in March 200 4 and 20 species recorded in July 2004.Out of total; bird species 33.94%were migratory, 25.68% were resident, 24.77% were winter visitors and 15.96%were summer visitors. On the basis of abundance, 41.28%were scarce, 22.9 % were occasional, 21.1%were fairly common and 14.6%were common. The Lake area was found to be rich in avian diversity although the Lake was not fully rehabilitated. Key words: Avian diversity, Chimdi Lake, seasonal status doi:10.3126/on.v5i1.802 Our Nature (2007)5:75-80